Mutations in TOPORS cause autosomal dominant retinitis pigmentosa with perivascular retinal pigment epithelium atrophy. - Chakarova, C; Papaioannou, MG; Khanna, H; Lopez, I; Waseem, N; Shah, A; Theis, T; Friedman, J; Maubaret, C; Bujakowska, K; Veraitch, B; El-Aziz, A; et al. (2007)
We report mutations in the gene for topoisomerase I-binding RS protein (TOPORS) in patients with autosomal dominant retinitis pigmentosa (adRP) linked to chromosome 9p21.1 (locus RP31). A positional-cloning approach, together with the use of bioinformatics, identified TOPORS (comprising three exons and encoding a protein of 1,045 aa) as the gene responsible for adRP. Mutations that include an insertion and a deletion have been identified in two adRP-affected families--one French Canadian and one German family, respectively. Interestingly, a distinct phenotype is noted at the earlier stages of the disease, with an unusual perivascular cuff of retinal pigment epithelium atrophy, which was found surrounding the superior and inferior arcades in the retina. TOPORS is a RING domain-containing E3 ubiquitin ligase and localizes in the nucleus in speckled loci that are associated with promyelocytic leukemia bodies. The ubiquitous nature of TOPORS expression and a lack of mutant protein in patients are highly suggestive of haploinsufficiency, rather than a dominant negative effect, as the molecular mechanism of the disease and make rescue of the clinical phenotype amenable to somatic gene therapy.